Literature Review : Relationship Between Moyamoya Disease And Cerebral Iscemic Incidents - Muh. Fawwaz Irhadi; Mochammad Erwin Rachman; Cahyono Kaelan (Jurnal EduHealth, 2024)
Moyamoya disease is a rare progressive cerebrovascular disorder characterized by blockage of arteries at the base of the brain, causing ischemic and hemorrhagic strokes. This condition is most common in children and adults in Asia, with the main symptoms being transient ischemic attacks (TIAs) or strokes. This study used a literature review method by collecting data from various medical journals related to the diagnosis and management of Moyamoya. Diagnosis is generally made through MRI, MRA, and DSA, with DSA being the best method to identify arterial stenosis and collateral formation. The results showed that treatment included medical therapy with aspirin and surgical revascularization procedures to improve cerebral blood flow, where direct revascularization provides faster results although technically more difficult. Early diagnosis and surgical intervention are essential to prevent disease progression.